Sparse bounds for Bochner–Riesz multiplers - Lacey, Michael T. (2019)
The Bochner–Riesz multipliers are shown to satisfy a range of sparse bounds. The range of sparse bounds increases to the optimal range, as δ increases to the critical value, even assuming only partial information on the Bochner–Riesz conjecture in dimensions n≥3. In dimension n=2, we prove a sharp range of sparse bounds. The method of proof is based upon a ‘single scale’ analysis, and yields the sharpest known weighted estimates for the Bochner–Riesz multipliers in the category of Muckenhoupt weights.